RHETORICAL LECTURE STRATEGIES IN INCREASING THE CONFIDENCE OF SPEAKING IN FRONT OF THE PUBLIC OF INDONESIAN LANGUAGE STUDENTS - Eva Juliana; Efridawati Harahap; Sulham Efendi Hasibuan (Jurnal Hata Poda, 2026)
Public speaking skills are crucial competencies for students of the Indonesian Language TadrisStudy Program as prospective educators. However, symptoms of communication anxiety(glossophobia) are still often the main obstacles in the learning process. This study aims toanalyze Rhetorical lecture strategies that are effective in increasing student confidence whenspeaking in public. Using a descriptive qualitative method with a case study approach, datawas collected through participatory observation, in-depth interviews with the teaching lecturer,and filling out an open questionnaire by students. The results showed that the integration ofcognitive strategies (restructuring of negative thoughts), physiological strategies (vocal anddiaphragmatic breathing techniques), and practical techniques (periodic speech simulation andpeer-feedback) in Rhetoric classes was able to significantly reduce anxiety. The implication ofthis study emphasizes that the Rhetoric course does not only function as a transfer of linguistictheoretical knowledge, but also as a space for adaptive mental conditioning to form thecommunication performance of professional teacher candidates